Indexes to the evidence [electronic resource] - British and American Joint Commission for the Final Settlement of the Claims of the Hudson's Bay and Puget's Sound Agricultural Companies. ([S.l. : s.n.)
Title taken from the last frame of the text. Cover title: Index to testimony for the claimant in the matter of the Hudson's Bay Company against the United States. Electronic reproduction. Mode of access: Internet. 44